Aristocratic Education and the Making of the American Republic - Boonshoft, Mark (The University of North Carolina Press, 2020)
"This book explains the rise, significance, and legacy of one of the most ubiquitous, significant, but forgotten institutions of early American life: the secondary school academy. Writing in 1788, Noah Webster bemoaned that in the United States "the constitutions are republican, [while] the laws of education are monarchical." Instead of building public, common school systems aimed at fostering a widely informed citizenry, the Federalists in power founded academies. These privately run but state-chartered secondary schools offered a Europe-style education directed primarily at elites. The Federalists' nation-building project, it turns out, depended on these reactionary schools to simultaneously reestablish rule by a traditional elite and legitimize the hierarchy. This, they believed, was necessary to make both the proposed constitutional system function and the United States into a world power. The reaction against this aristocratic educational system helped transform education from a tool of elite privilege into a key component of self-government. Ultimately, reformers successfully argued that the revolutionary promise of equal citizenship required genuinely common, public education. Academies, though, undermined republican ideals. In their curriculum, pedagogy, and culture, academies looked to many Americans like a caricature of education in aristocratic Europe. Even the legal basis for academies-charters of incorporation-screamed of monarchy. Charters had long been a privilege granted by the king. By tracing the history of academies in the revolutionary era, Boonshoft offers a new understanding of the cultural origins of the Federalists' national vision, the nature of the American revolutionary settlement, and, in turn, the origins of public education"--